2006
DOI: 10.1677/joe.1.06609
|View full text |Cite
|
Sign up to set email alerts
|

The restricted potential for recovery of growth plate chondrogenesis and longitudinal bone growth following exposure to pro-inflammatory cytokines

Abstract: Childhood chronic inflammatory disease can be associated with transient and permanent growth retardation. This study examined the potential for spontaneous growth recovery following pro-inflammatory cytokine exposure. Murine ATDC5 chondrogenic cells and postnatal metatarsals were exposed to interleukin (IL)-1 , IL-6 and tumour necrosis factor-(TNF ), and their growth and proliferative capacity were determined following recovery. TNF and IL-1 reduced chondrocyte proliferation and aggrecan and collagen types II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 36 publications
6
110
1
Order By: Relevance
“…Standardisation of [ 3 H]thymidine uptake to protein content (Phornphutkul et al 2006) confirms that an actual reduction in proliferation was observed following ceramide exposure, rather than solely a reduced uptake due to fewer cells through increased apoptosis. Both TNF-a and IL-1b exposure have also been reported to inhibit proliferation and induce apoptosis in ATDC5 cells (MacRae et al 2006b), and the results of this present study now suggest that ceramide may be acting as a second messenger in both processes. Both IL-1b and TNFa have also been shown to markedly reduce the gene expression of collagen II, collagen X and aggrecan (MacRae et al 2006b), but in our present study ceramide did not alter the gene expression of markers of chondrogenesis and differentiation (sox 9, collagen II and collagen X).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Standardisation of [ 3 H]thymidine uptake to protein content (Phornphutkul et al 2006) confirms that an actual reduction in proliferation was observed following ceramide exposure, rather than solely a reduced uptake due to fewer cells through increased apoptosis. Both TNF-a and IL-1b exposure have also been reported to inhibit proliferation and induce apoptosis in ATDC5 cells (MacRae et al 2006b), and the results of this present study now suggest that ceramide may be acting as a second messenger in both processes. Both IL-1b and TNFa have also been shown to markedly reduce the gene expression of collagen II, collagen X and aggrecan (MacRae et al 2006b), but in our present study ceramide did not alter the gene expression of markers of chondrogenesis and differentiation (sox 9, collagen II and collagen X).…”
Section: Discussionsupporting
confidence: 75%
“…Both TNF-a and IL-1b exposure have also been reported to inhibit proliferation and induce apoptosis in ATDC5 cells (MacRae et al 2006b), and the results of this present study now suggest that ceramide may be acting as a second messenger in both processes. Both IL-1b and TNFa have also been shown to markedly reduce the gene expression of collagen II, collagen X and aggrecan (MacRae et al 2006b), but in our present study ceramide did not alter the gene expression of markers of chondrogenesis and differentiation (sox 9, collagen II and collagen X). This suggests that ceramide generation does not affect differentiation in growth plate chondrocytes.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Then, we examined the expression of genes encoding cytokines that were reported to affect endochondral ossification. 17,[29][30][31] As shown in Figure 6c, among the cytokines examined, Il-1β and Mcp-5 displayed big differences between Ikkβ Prx1KO and control mice. Although IL-1β is reported to inhibit the differentiation of chondrocytes, 29,32 it was downregulated in the perichondrium of Ikkβ Prx1KO mice and thus fails to explain the phenotype.…”
Section: Resultsmentioning
confidence: 86%